Boundaries of Confidentiality in Mediation and the Mediator as a Guardian of Confidentiality Principle - Javakhishvili, Mariam; Tsiklauri, Salome (Alternative Dispute Resolution Yearbook, 2020)
Annotation is available in Georgian